PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR TEMATIK MUATAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN SISWA KELAS III SE-GUGUS 3 SANDEN BANTUL - Handin Handin; Nadziroh Nadziroh (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
This study aims to determine the differences in learning outcomes of PPKn subjects between scramble learning model classes and direct instruction model classes. This type of research is quasi-experiment. The results showed that the learning outcomes of PPKn subjects were taught using a higher scramble learning model while those taught using the direct instruction model were lower. The Z test results obtained Zhitung = 4,2790 and Ztable = 1,645. From the results of the Z test, it can be concluded that Zhitung> Ztable, means that there are differences in learning outcomes of PPKn Subjects between scramble learning model classes and direct instruction model classes. Based on the results of the Z test, it can be concluded that the scramble learning model is more influential than the direct instruction model on the learning outcomes of PPKn Subjects.Â